(untitled) (Research, Society and Development, 2021)
Communication through speech is the main way human beings express themselves and practice their interaction with individuals around them. However, there are situations in which the individual becomes unable to communicate. This is what happens when he is affected by cerebral palsy, considering that it is one or more damage to the brain that prevents the person from practicing various activities and social, cognitive, mobility activities, among others. Thus, the emergence of assistive technologies came to promote, through specific techniques, alternative communication to these people and, thus, make them more independent and autonomous, in social and emotional aspects. In this work, we present a conceptual review on Assistive Technology and its main characteristics, as well as a study about the human-machine relationship and how it influences human life, especially that of people with cerebral palsy.